Mail management system - Siti Nur Fathiah, Adnan (2015)
Management of records and details information is a crucial part in any organization. The purpose of such management is to ensure the traceability towards details that had been kept should there is needs to use it any time in the future. Mails record are usually recorded manually in a record book. The common problem faced with the manual records is it is outdated and finding of records are difficult and time consuming. Apart from that, the possibility that the record kept are loss or damage is high because physical records requires more attention in terms of ensuring the spaces provided for them is not preoccupied with other documents to prevent any mixed up of records. Besides that, it is difficult to hand over mails item to intended staff due to the needs to call each staff to acknowledge them regarding received mails. This problem consumed time and delayed the process of handling items to the receiver. The purpose of this thesis is to study and analyse mail system at IBS Technology Kuala Lumpur and to develop a computerized mail system according to user requirement. The methodology used for this study is Scrum in Agile Methodology which generally allows the system to be developed flexibly and able to respond to changes made even during development of system. The system developed is tested by using User Acceptance Test (UAT) which is carried out to ensure the system is developed based on user requirement and to track any error or improper way of a system behaviour so that correction can be made before implementation. The final result of the study is the implementation of the Mail Management System (MMS). The system is developed fully and record is kept in the system and searching of record can be made by different criteria.